Ferrocene doped ZIF-8 derived Fe-N-C single atom catalyst to active peroxymonosulfate for removal of bisphenol A - Huang, Zhikun; Yu, Haojie; Wang, Li; Wang, Mingyuan; Liu, Xiaowei; Shen, Di; Shen, Sudan; Ren, Shuning; Lin, Tengfei; Lei, Shuangying (Separation and purification technology, 2023)
•The Fe content of Fe-N-C SACs can be precisely controlled during synthesis process.•The BPA can be removed entirely within 10 min using low content of Fe-N-C SACs.•The optimal apparent rate constant of Fe-N-C was 9.48 times faster than that of N-C.•The interactions between Fe-N-C and PMS/BPA were studied by DFT calculations. Heterogeneous advanced oxidation process (AOP) technique exhibits a great potential to degrade recalcitrant and toxic bisphenol A (BPA) in water; however, traditional catalysts seriously suffer from agglomeration, leaching of active metal ions and poor stability. Herein, a serial of single atom catalysts (SACs) based on single Fe atoms anchored on N-doped porous carbon matrix (Fe-N-C) were successfully prepared through simple pyrolysis method. The Fe content of Fe-N-C could be accurately controlled by changing the doped ferrocene (Fc) in ZIF-8 precursor. The obtained Fe-N-C exhibited outstanding catalytic activity to active peroxymonosulfate (PMS) for BPA degradation, 94.3% BPA could be removed within 10 min, the reaction rate constant (k) of Fe-N-C reached to 0.395 min−1, which was 9.5 times faster than that of counterpart N-C, which derived from the synergistic effect of radical pathway, non-radical pathway and electron-transfer. In Fe-N-C/PMS system, the singlet oxygen (1O2) has been proved as the main reactive oxygen species (ROS) to dominate the BPA degradation process. Besides, the Fe-N-C/PMS and Fe-N-C/BPA interfacial interactions were investigated by density functional theory (DFT) calculations, which disclosed the formation of high-valent iron-oxo species (Fe(IV)=O) and interfacial electron-transfer to comprehensively and thoroughly investigate the mechanism of BPA degradation. This work aims to providing novel insight for investigation of BPA degradation mechanism in AOP system.